Content Analysis of English Language Teaching Materials in The Food and Beverage Industry - Abdul Syahid; Aulia Rahmi; Nuralisa Nuralisa; Wafa Qaulan Syahida; Rizki Hasanah (BADAN PENERBIT STIEPARI PRESS, 2024)
This article discusses Content Analysis of English Language Teaching Materials in the Food and Beverage Industry. This research method uses descriptive research method. The results showed that the book